Hospital Management Information System (SIMRS) in Improving Service Quality at Ogan Ilir Regional Hospital: Sistem Informasi Manajemen Rumah Sakit (SIMRS) dalam Meningkatkan Mutu Pelayanan di RSUD Ogan Ilir - Pusdikasari, Intan (Universitas Muhammadiyah Sidoarjo, 2025)
Hospital Management Information System plays an important role in supporting the overall process in the hospital with information technology. This study examines the role of SIMRS in improving the quality of service at Ogan Ilir Regional Hospital. This study aims to assess the effectiveness of SIMRS in streamlining hospital operations, improving patient care, and facilitating better data management. A qualitative approach was used, which included interviews with hospital staff and analysis of hospital performance metrics before and after the implementation of SIMRS. The results showed that SIMRS made a significant contribution to improving the quality of service by reducing administrative errors, increasing the efficiency of patient management, and providing real-time access to patient data. This study provides valuable insights for hospital management and policy makers who want to improve health service delivery through the use of information systems.